2017
DOI: 10.1080/15384047.2017.1373212
|View full text |Cite
|
Sign up to set email alerts
|

Expression ofSESN1, UHRF1BP1, and miR-377-3p as prognostic markers in mutatedTP53squamous cell carcinoma of the head and neck

Abstract: The tumor suppressor gene TP53 is the most frequently mutated gene in human papillomavirus (HPV)-negative head and neck squamous cell carcinoma (HNSCC). It represents a known transcription factor that controls different microRNAs (miRNA) and target genes involved in the regulation of cellular stress, apoptosis and response to DNA damage. We used The Cancer Genome Atlas database to investigate the difference in transcriptome and proteome levels between mutated and wild-type TP53 HPV-negative HNSCC. Using differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 91 publications
1
20
0
Order By: Relevance
“…To determine whether the above miRNAs were regulated by p53, the differential expression of these mirnas in p53 +/+ , p53 +/and p53 -/-mBM-MScs was investigated. The results revealed that mir-3152 and mir-377 were highly expressed in p53 +/and p53 -/-mBM-MScs, which is consistent with their expression levels in other types of cancer (28)(29)(30)(31)(32) and suggested that they served an oncogenic role following p53 inactivation. conversely, mir-221, mir-155 and mir-4669 expression levels were observed to be decreased in p53 +/and p53 -/-mBM-MSCs, which based on previous studies (32)(33)(34)(35)(36)(37)(38)(39), suggested that they may serve a tumor suppressive role in MSCs.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…To determine whether the above miRNAs were regulated by p53, the differential expression of these mirnas in p53 +/+ , p53 +/and p53 -/-mBM-MScs was investigated. The results revealed that mir-3152 and mir-377 were highly expressed in p53 +/and p53 -/-mBM-MScs, which is consistent with their expression levels in other types of cancer (28)(29)(30)(31)(32) and suggested that they served an oncogenic role following p53 inactivation. conversely, mir-221, mir-155 and mir-4669 expression levels were observed to be decreased in p53 +/and p53 -/-mBM-MSCs, which based on previous studies (32)(33)(34)(35)(36)(37)(38)(39), suggested that they may serve a tumor suppressive role in MSCs.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, mir-3152 is involved in the therapeutic response to neoadjuvant radio-chemotherapy resistance observed in squamous cell carcinoma of esophagus (eScc), which suggested that miR-3152 could act as a predictive biomarker for pre-therapeutic patient selection (28). mir-377 drives malignant characteristics and acts as a prognostic biomarker in multiple different cancers (29)(30)(31)(32), whereas mir-221 is involved in osteosarcoma and Gc progression (33,34). mir-155 has previously been observed to regulate melanoma cell growth by acting as a tumor suppressor (35), and it is overexpressed in hematological malignancies and solid tumors (36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MiR-377-3p, mentioned as a tumor suppressor in many literature studies, negatively regulates glioma cell proliferation and migration 37 and is a prognostic marker in squamous cell carcinoma. 38 Moreover, miR-377-3p is also involved in some stem cell differentiation. 39 The specic functions of miR-377-3p in a great deal of human cancers have been identied; however, limited data are available about its changes and roles in cutaneous malignant melanoma.…”
Section: Discussionmentioning
confidence: 99%